Delayed Gut Colonization Changes Future Insulin Resistance and Hepatic Gene Expression but Not Adiposity in Obese Mice - Maria B. B. Ebert; Caroline M. J. Mentzel; Anders Brunse; Lukasz Krych; Camilla H. F. Hansen (Journal of Obesity)
Objective. The importance of early microbial dysbiosis in later development of obesity and metabolic disorders has been a subject of debate. Here we tested cause and effect in mice. Methods. Germ-free male Swiss Webster mice were colonized in a specific-pathogen-free (SPF) facility at 1 week (1W) and 3 weeks (3W) of age. They were challenged with a high-fat diet and their responses were compared with SPF mice. Gut microbiota was analyzed by 16S rRNA gene sequencing. Moreover, RNA sequencing of the liver was performed on additional 3W and SPF mice on a regular chow diet. Results. There were no significant differences in weight, food consumption, epididymal fat weight, HbA1c levels, and serum insulin and leptin, whereas the early germ-free period resulted in mice with impaired glucose tolerance. Both the 1W and 3W group peaked 56% (p<0.05) and 66% (p<0.01) higher in blood glucose than the SPF control group, respectively. This was accompanied by a 45% reduction in the level of the anti-inflammatory cytokine IL-10 in the 1W mice (p<0.05). There were no differences in the gut microbiota between the groups, indicating that all mice colonized fully after the germ-free period. Marked effects on hepatic gene expression (728 differentially expressed genes with adjusted p<0.05 and a fold change ± 1.5) suggested a potential predisposition to a higher risk of developing insulin resistance in the 3W group. Conclusions. Lack of microbes early in life had no impact on adiposity but led to insulin resistance and altered liver gene expression related to glucose metabolism in mice. The study strongly supports the notion that microbial signaling to the liver in the beginning of life can alter the host’s risk of developing metabolic disorder later in life.